Therapeutic Activity of Lenalidomide in Mantle Cell Lymphoma and Indolent Non-Hodgkin’s Lymphomas - Marco Gunnellini; Lorenzo Falchi (Advances in Hematology)
Mantle cell lymphoma (MCL) comprises 3–10% of NHL, with survival times ranging from 3 and 5 years. Indolent lymphomas represent approximately 30% of all NHLs with patient survival largely dependent on validated prognostic scores. High response rates are typically achieved in these patients with current first-line chemoimmunotherapy. However, most patients will eventually relapse and become chemorefractory with poor outcome. Alternative chemoimmunotherapy regimens are often used as salvage strategy and stem cell transplant remains an option for selected patients. However, novel approaches are urgently needed for patients no longer responding to conventional chemotherapy. Lenalidomide is an immunomodulatory drug with activity in multiple myeloma, myelodisplastic syndrome and chronic lymphoproliferative disorders. In phase II studies of indolent NHL and MCL lenalidomide has shown activity with encouraging response rates, both as a single agent and in combination with other drugs. Some of these responses may be durable. Optimal dose of lenalidomide has not been defined yet. The role of lenalidomide in the therapeutic armamentarium of patients with indolent NHL or MCL will be discussed in the present paper.